Data envelopment analysis of efficiency of real estate investment trusts in Singapore - Mohamad, Azhar (Emerald, 2017)
In this study, we employ data envelopment analysis to assess the technical efficiency andperformance of real estate investment trusts (REITs) in Singapore, for the years 2009 through 2013. We apply the Malmquist Productivity Index to express the productivity change of the REITs over time. We find that whilst most REITs have experienced efficiency improvements, there has been little productivity growth at the frontier during the study period. The finding indicates that it is possible to improve the performance of the REITs by further improving technological efficiency, since technological regress has been the main reason for the poor productivity growth of the REITs in Singapore.